Nonaqueous capillary electrophoresis mass spectrometry method for determining highly hydrophobic peptides. Issue 9 (31st October 2017) - Cheng, Jianhui; Chen, David D. Y.
Abstract: A nonaqueous capillary electrophoresis mass spectrometry (NACE‐MS) method was developed to separate and determine highly hydrophobic temporin peptides. The nonaqueous background electrolyte solution was a mixture of 20% acetonitrile, 78% methanol and 2% formic acid, with 20 mM ammonium formate. The separation of six peptides was completed within 12 min. The CE system was connected to a triple quadrupole mass spectrometer operating in MRM mode using a chemical modifier solution of 2 mM ammonium formate in ethanol with the flow through microvial interface. The mass spectrometer offered a second dimension of separation for peptides having identical migration times but different structures. The new method represents the first system capable of reliably determining hydrophobic peptides without using reversed phase liquid chromatography mass spectrometry.